Relationship Between a Reflective-Formative Model of Team Brand Associations and Behavioral Intentions: The Mediating Effect of Fan Identification - Ho Yeol Yu; Neal Ternes; Claudia B Ambs; Sanghoon Kim (Journal of Applied Sports Management, 2022)
Understanding fans’ perceived associations with their favorite teams is crucial for the successful management of sport teams. In the current study, team brand associations are measured as a reflective-formative construct to examine the role of the fan identification on the relationship between team brand associations and behavioral intentions. Data from professional soccer spectators (n = 101) were analyzed using PLS-SEM. The results indicated that the reflective-formative construct of team brand associations and fan identification influence behavioral intention, whilst fan identification was found to mediate the relationship between team brand associations and behavioral intentions. Managerial implications include strategic marketing how sport team managers can alter their team brand associations to foster the relationship between fans and teams.
Keywords: Team Brand Associations; Fan Identification; Reflective-Formative Model